PENGARUH KECUKUPAN MODAL DAN KOMPETISI TERHADAP PROFITABILITAS BANK SYARIAH DI INDONESIA - Mauliza, Dessy; Daud, Rulfah M. (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2016)
This study is conducted to analyze the influence of capital adequacy and competition against sharia banks profitability. This study applied census method , where studys population was all sharia bank enlisted in Bank of Indonesia within 2013 until 2015 period. Data used in this study were secondary data.Results of this study show that capital adequacy and competition together influenced sharia banks profitability. Partially, capital adequacy had negative influence against banks profitability while competition had positive influence against sharia banks profitability.Keywords Capital Adequacy Ratio, Competition, Profitability (ROA).